Evaluation of local invasion by oesophageal carcinoma—a prospective study of prone computed tomography scanning. Issue 905 (1st March 2001) - Wayman, J; Chakraverty, S; Griffin, S M; Doyle, G J; Keir, M J; Simpson, W
Abstract : The aim of this study was to assess the value of prone computed tomography compared with the traditional supine position, in the assessment of invasion of adjacent mediastinal structures by oesophageal cancer. A prospective, single blind case-case comparative study of signs of local tumour invasion was conducted. Sixty nine consecutive patients undergoing computed tomography for preoperative staging of oesophageal carcinoma were studied. Computed tomography scanning of the thorax was performed in the standard supine followed by prone position; in 39 patients the computed tomography findings were correlated with the surgical findings. Four established radiological signs used to assess mediastinal invasion were scored in each case. Based on the radiological scoring system, there was a significant down staging in the probability of aortic invasion in 12 of the 69 cases (p<0.05). A similar improvement in accuracy was seen in the cases undergoing surgery; of the 38 cases who did not have aortic invasion at operation, 10 cases were scored as high for aortic invasion on the supine scans compared with only three on the prone position (p<0.05). Prone scanning was not of significant additional value in the assessment of major airway or pericardial invasion. Modification of the computed tomography protocol to include scanning in the prone position will improve the accuracy of the preoperative staging of patients with oesophageal malignancy and reduce the chance of overstaging disease. Especially in centres where endoscopic ultrasound is not available, our modification may reduce the chance of denying patients potentially curative operations.